(untitled) (Research, Society and Development, 2021)
Introduction: The onset of Systemic Lupus Erythematosus (SLE), after 50 years of age, occurs in 3 to 18% of patients and is called Lupus Late or Lupus Senile (LESS). Objective: to describe the clinical case of a patient diagnosed with Senile Systemic Lupus Erythematosus who was admitted to the Doctor Waldemar de Alcântara General Hospital, in addition to conducting a literature review on the subject in order to share the experience and knowledge obtained with the medical community. Methods: Descriptive study of the case report type, using information obtained through interaction with the patient during hospitalization, as well as data obtained from the medical record of the results of laboratory tests and images. Discussion: The severity of lupus decreases with age. Some studies have shown that patients with late-onset SLE have less specific organ involvement compared to early-onset patients. Likewise, they more often present with serositis, Sjögren’s syndrome and neurological manifestations. Conclusion: Although rare, the diagnostic hypothesis of LESS should be considered as a differential diagnosis. For this, it is necessary to request na early FAN (antinuclear factor), which is a mandatory criterion for lupus. Given the early diagnosis of LESS, the patient can benefit from a shorter hospital stay, in addition to avoiding the use of unnecessary medications.